The challenge of Jesus' parables - Longenecker, Richard N.; H.H. Bingham Colloquium in New Testament 1998 : McMaster Divinity College) (Michigan : Grand Rapids : William B. Eerdmans Publishing Company, 2000)
"The Parables recorded in the Gospels are central to an understanding of Jesus and his ministry, and their teachings form, in large part, the heart of the Christian gospel. Though commonly assumed to be simple, easily understood stories, the parables actually present a number of complex challenges to modern readers hoping to fully grasp their meaning. In this book thirteen first-rate New Testament scholars clear the way to the proper meaning and application of the parables by presenting Jesus' teachings in their original context. Providing a more responsible treatment of the parables than they usually receive in scholarly writings or the popular press, this volume will challenge anew those seeking to live more genuine lives as followers of Jesus."--Jacket.
From allegorizing to allegorizing: a history of the interpretation of the parables of Jesus / Klyne R. Snodgrass -- Genre of the parables / Robert H. Stein -- Parables in early Judaism / Craig A. Evans -- Mark's parables of the kingdom (Mark 4:1-34) / Morna D. Hooker -- Matthew's parables of the kingdom (Matthew 13:1-52) / Donald A. Hagner -- Luke's parables of the kingdom (Luke 8:4-15; 13:18-21) / Richard N. Longenecker -- Produce fruit worthy of repentance: parables of judgment against the Jewish religious leaders and the nation (Matthew 21:28-22:14 par.; Luke 13:6-9) / Allan W. Martens -- On being ready (Matthew 25:1-46) / Richard T. France -- Parables on God's love and forgiveness (Luke 15:1-32) / Stephen C. Barton -- Parables on poverty and riches (Luke 12:13-21; 16:1-13; 16:19-31) / Stephen I. Wright -- Parables on prayer (Luke 11:5-13; 18:1-14) / Walter L. Liefeld -- Strange neighbors and risky care (Matthew 18:21-35; Luke 14:7-14; Luke 10:25-37) / Sylvia C. Keesmaat -- Everyone who hears these words of mine: parables on discipleship (Matthew 7:24-27; Luke 6:47-49; Luke 14:28-33; Luke 17:7-10; Matthew 20:1-16) / Michael P. Knowles.
Proceedings of the 4th annual H.H. Bingham Colloquium in New Testament, held June 22-23, 1998 at McMaster Divinity College.
Includes bibliographical references.
Keywords: Jesus Christ -- Parables; Conference papers and proceedings